Life – Style of patients with peptic ulcer A case control study - al-ani, Samir; Jadoua, betool (Iraqi National Journal of Nursing Specialties, 2005)
Abstract A descriptive (retrospective) (a case-control) study was carried out at Al-Karama Teaching Hospital, Baghdad Teaching Hospital and Surgical Specialties Hospital, and Gastro-Intestinal Tract and Liver (GIT) Hospital for the period of December 1st, 2001 To March 15th 2002. To identify aspects of life-style that may contribute to the occurrence of peptic ulcer (P.U)as risk factors. And to find out the relationship between the demographic characteristic of the group. Non-probability (Purposive) sample of (100) cases who were admitted to the endoscopy department who were later on diagnosed as having peptic ulcer. The other (100) controls, were free of any gastrointestinal disorder. They were matched with the cases by age, gender, marital status, and occupation. Questionnaire was designed and comprised of (73) items. The reliability of the questionnaire(r=0.89). The data collected by use of interview and analyzed by using descriptive statistical analysis that include frequency, percentage, Mean, Mean of scores, pearson correlation coefficient, and inferential statistical analysis that include chi-square, t-teset, and stepwise multiple regression. The results revealed a significant relationship between life style and the occurrence of peptic ulcer and significant relationship between the demographic characteristics and the occurrence of peptic ulcer. The stady recommended that: Establishing specialized centers of gastro-Intestinal trackt in all governorates to present wide services to persons at risk of peptic ulcer and Education program should be designed to increase people information.